Stability Analysis of Methane Hydrate-Bearing Soils Considering Dissociation - Hiromasa Iwai; Sayuri Kimoto; Toshifumi Akaki; Fusao Oka (Energies, 2015)
It is well known that the methane hydrate dissociation process may lead to unstable behavior such as large ground deformations, uncontrollable gas production, etc. A linear instability analysis was performed in order to investigate which variables have a significant effect on the onset of the instability behavior of methane hydrate-bearing soils subjected to dissociation. In the analysis a simplified viscoplastic constitutive equation is used for the soil sediment. The stability analysis shows that the onset of instability of the material system mainly depends on the strain hardening-softening parameter, the degree of strain, and the permeability for water and gas. Then, we conducted a numerical analysis of gas hydrate-bearing soil considering hydrate dissociation in order to investigate the effect of the parameters on the system. The simulation method used in the present study can describe the chemo-thermo-mechanically coupled behaviors such as phase changes from hydrates to water and gas, temperature changes and ground deformation. From the numerical results, we found that basically the larger the permeability for water and gas is, the more stable the simulation results are. These results are consistent with those obtained from the linear stability analysis.